Structure of the Hungarian pension system and the most important features of the certain pillars with regard to the expectations of the EU - Barta, Judit (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Europe is facing a major demographic crisis, because longer lifespan, declining birth rates and an ageing society. This situation affects the state pension systems as well, which operation on the pay-as-you-go basis, because fewer and fewer young people will support more pensioner for a longer time. In addition to decreasing contribution and increasing payments, budget support will be needed. However, this has EU limitations. In the final case, this situation could lead to the reduction of the amount of state pensions, which could degrade the previous replacement rate. According to predictions in most Member States an supplementary pension will be required to ensure old-age living. In this regard the EU has set out its expectations. The study examines that how can the institutions of the Hungarian supplementary pension system meet the expectations of the EU in the light of legal regulations.